Arm Ergometry to Improve Mobility in Progressive Multiple Sclerosis (AMBOS)—Results of a Pilot Randomized Controlled Trial - Heinrich, Inga; Rosenthal, Friederike; Patra, Stefan; Schulz, Karl-Heinz; Welsch, Götz H.; Vettorazzi, Eik; Rosenkranz, Sina C.; Stellmann, Jan Patrick; Ramien, Caren; Pöttgen, Jana; Gold, Stefan M.; Heesen, Christoph (Frontiers in Neurology, 2021)
Background: Walking disability is one of the most frequent and burdening symptoms of progressive multiple sclerosis (MS). Most of the exercise intervention studies which showed an improvement in mobility performance were conducted in low to moderately disabled relapsing-remitting multiple sclerosis patients with interventions using the legs. However, MS patients with substantial walking disability hardly can perform these tasks. Earlier work has indicated that aerobic arm training might also improve walking performance and could therefore be a therapeutic option in already moderately disabled progressive MS patients. Methods: Patients with progressive MS and EDSS 4-6.5 were randomized to either a waitlist control group (CG) or an intervention group (IG). The IG performed a 12-week home-based, individualized arm ergometry exercise training program. Maximum walking distance as measured by the six-minute-walking test (6MWT) was the primary endpoint. Secondary endpoints included aerobic fitness, other mobility tests, cognitive functioning as well as fatigue and depression. Results: 53 patients with moderate disability (mean EDSS 5.5, SD 0.9) were included. Patients in the IG showed strong adherence to the program with a mean of 67 (SD 26.4) training sessions. Maximum work load (Pmax) increased in the training group while other fitness indictors did not. Walking distance in the 6MWT improved in both training and waitlist group but not significantly more in trained patients. Similarly, other mobility measures showed no differential group effect. Cognitive functioning remained unchanged. Conclusion: Although maximum work load improved, three months of high frequency arm ergometry training of low to moderate intensity could not show improved walking ability or cognitive functioning in progressive MS compared to a waitlist control group. The study was registered at www.clinicaltrials.gov (NCT03147105).